Feeding behaviour of grazing and zero-grazing goats fed with the same herbage - Claps S.; Rubino R.; Fedele V. (Recent advances in small ruminant nutrition, 1997)
The aim of this experiment was to investigate the influence of the different modalities of herbage utilisation on goat feeding behaviour. The experiment was carried out at the beginning of spring. Two groups of six dry goats were used. The first group (Grazing) grazed for eight hours per day a native pasture, the second one (zero-grazing), allocated in metabolic cages, was fed with the same herbage of the first group offered ad libitum. The percentage of grasses and forbs species was not influenced by herbage utilisation modalities, on the contrary, that of the legumes was influenced. The diet was poorer in legumes in the grazing group than in the zero-grazing one. Despite the lower percentage of legumes in the grazing goats, crude protein (CP) content was about 6 per cent higher in the grazing group. On the other hand, neutral detergent fibre (NDF) and crude fibre (CF) were 5 and 7 points higher in the zero-grazing group. The results of this research show that the selective ability of zero-grazing goats was much lower than that of grazing goats.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)